Efficacy of oral erythromycin for treatment of feeding intolerance in preterm infants - Pracha Nuntnarumit (2018)
Objective: To determine the efficacy and safety of oral erythromycin (EM) for feeding intolerance in preterm infants < 35 weeks gestation. Study design: In this randomized, double-blinded, placebo-controlled trial, preterm infants with feeding intolerance were randomly allocated to a treatment group given EM ethyl succinate 10 mg/kg every 6 hours for 2 days, followed by 4 mg/kg every 6 hours for another 5 days, or to a control group given placebo. The primary outcome was time to full feeding (150 mL/kg/day) after the start of treatment. Results: Each group comprised 23 preterm infants, almost all of whom were < 32 weeks gestation. Baseline characteristics were similar between the 2 groups. Times to full feeding were significantly shorter and the number of withheld feeds were significantly less in the EM group than the control group; the respective medians (interquartile ranges) were 7 days (6 to 9 days) versus 13 days (9 to 15 days) (P < .001) and 1 episode (0 to 2 episodes) versus 9 episodes (2 to 13 episodes) (P < .001). No significant differences in episodes of sepsis, necrotizing enterocolitis, and cholestasis were observed. Conclusions: Oral EM was effective and safe for treatment of feeding intolerance in preterm infants. © 2006 Elsevier Inc. All rights reserved.